2011
DOI: 10.1111/j.1525-1594.2011.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrionatriuretic Peptide Improves Left Ventricular Function After Myocardial Global Ischemia–Reperfusion in Hypoxic Hearts

Abstract: Atrionatriuretic peptide (ANP) is reported to be useful for attenuating myocardial ischemia-reperfusion injury and improving left ventricular function after reperfusion. However, ANP may be either ineffectual or harmful in cases where the myocardium has been chronically hypoxic since birth. This can be a result of the concomitant high levels of cyclic guanosine monophosphate (cGMP) produced within the myocardium. This study aimed to verify the validity of using ANP to improve left ventricular function after my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Similarly, in studies performed in isolated perfused rat hearts, BNP and ANP prevented cardiac reperfusion injury after coronary occlusion and improved left ventricular function after cardiac global ischemia-reperfusion when added to the perfusion solution (Table 1). 52,71,73,75 In concordance with the ex vivo studies, in vivo studies in rats subjected to coronary occlusion (30 min) and reperfusion (4 h) showed that infusion of BNP (0.03 mg/kg min, i.v. ), starting 15 min before reperfusion until the end of reperfusion, decreased the IS/AAR ratio by approximately 50%.…”
Section: Infarct-reducing Effect Of Natriuretic Peptidessupporting
confidence: 62%
“…Similarly, in studies performed in isolated perfused rat hearts, BNP and ANP prevented cardiac reperfusion injury after coronary occlusion and improved left ventricular function after cardiac global ischemia-reperfusion when added to the perfusion solution (Table 1). 52,71,73,75 In concordance with the ex vivo studies, in vivo studies in rats subjected to coronary occlusion (30 min) and reperfusion (4 h) showed that infusion of BNP (0.03 mg/kg min, i.v. ), starting 15 min before reperfusion until the end of reperfusion, decreased the IS/AAR ratio by approximately 50%.…”
Section: Infarct-reducing Effect Of Natriuretic Peptidessupporting
confidence: 62%
“…ANP and BNP are closely related to MIR, and ANP was shown to improve cardiac function by promoting the release of cGMP in isolated hypoxic reperfusion rat heart [39]. ANP/PKG signaling pathway can regulate the K ATP channel of ventricular cardiomyocytes [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many effects, including hypoxia, stimulate secretion (Casserly et al, 2010). The stimulating effect of hypoxia on the release of ANP is proved (Fujii et al, 2011). It is also known that under the influence of hypoxia, transcription of the ANP increases by activation of HIFs (hypoxia inducible factors) (Patterson & Zhang, 2010).…”
Section: Fig 3 Representative Image Of Secretory Atrial Cardiomyocymentioning
confidence: 99%